Spn1, a multifunctional player in the chromatin context - Li, Sha, author; Stargell, Laurie, advisor; Argueso, J. Lucas, committee member; Hansen, Jeffrey, committee member; Luger, Karolin, committee member; Yao, Tingting, committee member (Colorado State University. Libraries, 2016)
Spn1 was initially identified as a transcription factor that copurified with Spt6. Spn1 functions in transcription initiation and elongation, mRNA processing and export, histone modification, as well as in heterochromatic silencing. Our recent study demonstrated that Spn1 could bind histones and assemble nucleosomes in vitro. Therefore, Spn1 is a new member of the histone chaperone family. Here we found that Spt6 regulates Spn1-nucleosome interaction and conversely, Spn1 regulates Spt6-H2A-H2B interaction. Co-regulation between Spn1 and Spt6 enables them to be independent histone chaperones in nucleosome assembly. In addition, abrogation of Spn1-Spt6 interaction does not generate cryptic transcripts at certain genes. Furthermore, we identified a new interaction between Spn1 and the histone chaperone Nap1. Spn1, Nap1 and histones can form a large complex. We also found Spt6 could compete Nap1 for Spn1 binding, therefore disrupting Spn1-Nap1 interaction and releasing Nap1. In sum, Spn1 plays a multifunctional role in the chromatin context via dynamic interactions with its binding partners.